Bedside Teaching and Respecting the Pediatric Patient: A Response to Verpaelst - Touyz, Sarah (BioéthiqueOnline, 2015)
Bedside teaching involving patients, physicians, and students is a ubiquitous technique used for medical training. Respect, valid informed consent, and transparency are key to ethical and effective teaching. Patient refusal in participating in bedside teaching must be respected. These ought to apply to patients of all ages, including children, who may not fully understand or be capable of consenting to participating in teaching.